The Relationship Between Job Insecurity and Employee Performance: A Systematic Literature Review and Research Agenda - Lopez-Bohle, S; Muñoz-Medina, L (Emerald Publishing, 2023)
Purpose: Although research on job insecurity (JI) and its relationship with employee performance has increased in recent years, results are mixed and inconclusive. The objectives of this paper are to explore 1) the conceptualizations of JI, 2) the relationship between JI and different performance dimensions, 3) the theoretical perspectives used to explain the JI–performance relationship and 4) the mechanisms and contextual boundaries that affect the JI–performance relationship. Design/methodology/approach: Following the PRISMA guidelines, the authors systematically searched for peer-reviewed empirical studies published before July 2021 in Web of Science and Scopus. The authors analyzed 81 empirical studies published on the conceptualization of job insecurity, its relationship with employee performance, and what mechanisms and contingency factors are studied. The authors used thematic analysis to analyze the articles. Findings: Results of this review show that the quantitative cognitive dimension is dominant in extant JI literature. Furthermore, in-role performance and OCB were most often investigated in relation to the four dimensions of job insecurity, drawing from a range of theoretical perspectives to explain this relationship. Moreover, a variety of mechanisms and contextual factors on individual, individual work-related, individual-level attitudes and job-level characteristics have found to play a role in this relationship. Research limitations/implications: This study has a number of limitations. The first pertains to the exclusion of articles in languages other than English and non-peer reviewed papers. It is possible that the search strategy used may not have identified other studies that may have met the established criteria in order to be included in our research. However, this method was chosen to guarantee the quality of the included articles in this study and in line with previous meta-analyses and literature reviews (De Witte et al., 2016; Sverke et al., 2019). Second, one selection criteria focused on how performance was assessed in the studies incorporated in this literature review. The authors excluded studies that addressed performance from the perspective of the organization (i.e. studies that measured performance at the organizational level). The authors herewith might have excluded studies that focused on one or multiple job insecurity constructs, but the authors herewith included studies that were comparable in terms of performance indicator outcomes. Future studies could expand the search by investigating, as a next step, the impact on organizational performance. Finally, since the focus of this literature review was on the relationship between job insecurity and performance indicators, including the mechanisms and boundary conditions that affect this relationship, the authors did not include focus on how job insecurity can be influenced (Shoss, 2017), and herewith lack information on the predictors side of job insecurity. However, by narrowing the authors focus to mediators and moderators, the authors were able to come up with an extensive list of factors that impact the job insecurity–performance relationship and herewith provide fruitful areas for future research. Future studies could expand these findings by providing an overview of predictors of different job insecurity constructs, to see whether there are potential different predictors of job insecurity conceptualizations (Jiang and Lavaysse, 2018). Practical implications: The study review contributes to the systematization of the current empirical evidence on this area of research. This is especially important and enables room to take an additional step toward understanding the consequences of job insecurity on performance. Specifically, it is important for organizations and policymakers to be aware of the different conceptualizations of job insecurity that exist and how they impact employee performance. In addition, an overview of potential mechanisms and boundary conditions that affect this relationship provides insights as to how organizations can intervene to affect reactions to job insecurity. Social implications: The study findings are relevant and may be of interest to decision makers in organizations and national authorities that must have information on quality concerning the effects of job insecurity on performance. Originality/value: Based on these findings the authors show the impact of the different conceptualizations of job insecurity and how they affect job performance. In addition, the authors provide recommendations for future studies how to better handle the integration of different conceptualizations and measures of job insecurity and its different approaches. © 2023, Emerald Publishing Limited.